High‐dose supplementation of selenium in left ventricular assist device implant surgery: A double‐blinded, randomized controlled pilot trial. Issue 6 (5th January 2022) - Laaf, Elena; Benstoem, Carina; Rossaint, Rolf; Wendt, Sebastian; Fitzner, Christina; Moza, Ajay; Zayat, Rashad; Hill, Aileen; Heyland, Daren K.; Schomburg, Lutz; Goetzenich, Andreas; Stoppe, Christian
Abstract: Background: Systemic inflammation and oxidative stress remain the main causes of complications in patients with heart failure receiving a left ventricular assist device (LVAD). Selenoproteins are a cornerstone of antioxidant defense mechanisms for improving inflammatory conditions. Methods: In a monocentric, double‐blinded pilot trial patients scheduled for LVAD implantation were randomized to receive 300 mcg of selenium orally the evening before surgery, followed by a high‐dose of intravenous selenium supplementation (3000 mcg after anesthesia induction, 1000 mcg upon intensive care unit [ICU] admission, and 1000 mcg daily in the ICU for a maximum of 14 days) or placebo. The main outcomes were feasibility and effectiveness in restoring serum selenium concentrations. Results: Twenty patients were included in the analysis. The average duration of study intervention was 12.6 days (7–14), with 97.7% dose compliance. No patient received open‐label selenium. The supplementation strategy was effective in compensating low serum selenium concentrations (before surgery: control, 63.5 ± 11.9 mcg/L vs intervention, 65.8 ± 16.5 mcg/L; ICU admission: control, 49.0 ± 9.8 mcg/L vs intervention, 144.2 ± 45.4 mcg/L). Serum selenium concentrations in the intervention group were significantly higher during the observation period (baseline: mean of placebo (MoP), 63.1 vs mean of selenium (MoS), 64.0; ICU admission: MoP, 49.0 vs MoS, 144.6; day 1‐13: MoP, 43.6‐48.5 vs MoS, 100.4‐131.0). Conclusion: Selenium supplementation in patients receiving LVAD implantation is feasible and effective to compensate a selenium deficiency.